A review of psychological research on kando as an inclusive concept of moving experiences - Yasuda, Shoko; Shoda, Haruka; Uemiya, Ai; Isaka, Tadao (Frontiers in Psychology, 2022)
We are emotionally moved when we give birth to a child, witness the triumph of an athlete, listen to a beautiful piece of music, and so forth. Such moving experiences have been described as a form of emotion, by terms such as being moved, awe, and kama muta, each of which have been studied as a separate, but interrelated, psychological phenomenon. Japanese people use the term kando to describe these experiences collectively. In this study, we propose that kando should be treated as an umbrella term covering being moved, awe, and kama muta. To this end, we reviewed the literature on kando conducted by Japanese researchers and compared it to relevant concepts, mainly examined in Western countries. We also reviewed the literature on the generative mechanism of kando, and established that emotional and physical reactions are important to determine the degree of kando across the cases with and without storyline. Furthermore, individual characteristics such as trait empathy may generate a stronger degree of kando. Kando experiences can affect subsequent behaviors and cognition, though we still need evidence that such change can be triggered genuinely by the experience of kando. We suggest that kando may make our neuro-cognitive network tend towards more direct, unconscious, and impulsive decision making. One of the remaining questions in this domain is whether the mental construct of kando can find an equivalent to people in Western countries. For this purpose, events and reactions relevant to kando experiences should be systematically collected from a broad population.